2014
DOI: 10.1509/jm.12.0344
|View full text |Cite
|
Sign up to set email alerts
|

When to Take or Forgo New Product Exclusivity: Balancing Protection from Competition against Word-of-Mouth Spillover

Abstract: Manufacturers or resellers introducing a new product often must decide whether and for how long to be its exclusive seller. Standard models of competition and conventional wisdom suggest that exclusivity boosts profits. However, using both agent-based simulations and game-theoretic modeling, the authors find that positive word of mouth (WOM) from customers of rival firms can make exclusivity unprofitable. This reversal of conventional wisdom occurs because WOM creates a positive externality, and a firm holding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 74 publications
0
9
0
Order By: Relevance
“…For example, Krishnan et al (2012) find that positive WOM about a product from rival loyalists benefits both sales of the focal firm and those of competitors by increasing overall category sales. Research has also shown that WOM from rival loyalists can directly benefit competitors' sales (Peres and Van den Bulte, 2014), or even lead to shorter new product take-off times (Libai et al, 2009). However, while this research reveals the possible benefits of WOM from rival loyalists, it has primarily focused on postrelease WOM, when the WOM is more likely to be based on real experiences and verifiable facts.…”
Section: Brand Communities and Word Of Mouthmentioning
confidence: 93%
“…For example, Krishnan et al (2012) find that positive WOM about a product from rival loyalists benefits both sales of the focal firm and those of competitors by increasing overall category sales. Research has also shown that WOM from rival loyalists can directly benefit competitors' sales (Peres and Van den Bulte, 2014), or even lead to shorter new product take-off times (Libai et al, 2009). However, while this research reveals the possible benefits of WOM from rival loyalists, it has primarily focused on postrelease WOM, when the WOM is more likely to be based on real experiences and verifiable facts.…”
Section: Brand Communities and Word Of Mouthmentioning
confidence: 93%
“…Another literature argues that sustainable advantage demonstrates the capability to anticipate environmental turbulence faster than the competitor (Kumar et al, 2011). The capability of small and medium enterprises (SMEs) to enhance their product development relies on a robust informal relationship with their stakeholders, which demonstrates their responsiveness to the needs of the customers (Perez & Bulte, 2014). Such capability includes collaboration for horizontal communication, stretch assignments, a risktolerant environment, and reduced centralised control (Maurer & London, 2018), which allows organisations to generate value-focused sales management in the industrial context (Töytäri & Rajala, 2015;Pratono et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The capability of small and medium enterprises (SMEs) to enhance their product development relies on social capital, which demonstrates a robust informal relationship with their stakeholders, which demonstrates their responsiveness to the needs of the customers (Perez & Bulte, 2014). Extensive business networking is essential for SMEs to acquire local knowledge for innovation development by increasing their managerial capability ties with their buyers and suppliers (Wang & Chung, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Since environmentally aware young residents -digital natives -are susceptible to sustainable solutions [Hackbarth, Madle ner, 2013], the very notion of the solution being sustainable may lead to their favourable attitude towards it. Since SC solutions/ smart solutions are commonly related to sustainability, the very notion of "smart" or "sustainable" as a brand might instigate their adoption, apart from other motivations, such as homophily [Aral, Walker, 2011;Susarla, Oh, 2012;Haenlein, 2013;Goel, Goldstein, 2014;Mor vin sky, Amir, Muller, 2017], signaling [Peres, Muller, Mahajan, 2010;Mathur, Chun, Ma heswa ran, 2016;, network externality [Peres, Muller, Mahajan, 2010;Aral, 2011;Haenlein, 2013], intrinsic and extrinsic motivation [Frey, Oberholzer-Gee, 1997;Edinger-Schons et al, 2018;Kumar et al, 2018], word-of-mouth (WOM) [Peres, Van den Bulte, 2014;Bol linger, Gillingham, 2012;Godes, Mayzlin, 2004], including electronic WOM [So, Oh, Min, 2018], monetary incentives [Lambrecht, Seim, Tucker, 2011;Beresteanu, Li, 2011], social norms [Langley et al, 2012; and others (for the overview of motivations vide Ap pendix).…”
Section: Human-driven Approach: Propositions Pertaining To Adoption Of Sc Solutions By Digital Nativesmentioning
confidence: 99%
“…[ Han, Gershoff, 2018] Stand to benefit, goal progress, proximity, framing of goal associated activities, and the presence of conflicting goals, mood maintenance [Weaver, Hamby, 2018] Social influence [Ajzen, 1991] Subjective norm, attitude, belief (salient beliefs: behavioral beliefs, normative beliefs, control beliefs) [Peres, Van den Bulte, 2014] Positive externality of social contagion, WOM, social-normative acceptability, legitimacy, concerns about social status, visual influence, exclusivity [Lee, Ofek, Steenburgh, 2017] WOM, search advertising, mass-invite, peer-to-peer actions [Murphy, Dweck, 2016] Mindsets are important because they shape people's motivation. Praises -for fixed minset, learning -for growth mindset.…”
Section: Appendix (Continued)mentioning
confidence: 99%